A length-adjustable vacuum-powered artificial muscle for wearable physiotherapy assistance in infants - Gollob, Samuel Dutra; Mendoza, Mijaíl Jaén; Koo, Bon Ho Brandon; Centeno, Esteban; Vela, Emir A.; Roche, Ellen T. (Frontiers in Robotics and AI, 2023)
Soft pneumatic artificial muscles are a large and growing class of actuators, with multiple benefits over traditional linear actuators. Their use of soft materials allows for light-weight, complex motions, and safe interfacing with humans, while preserving large contraction ratios, output force, and toughness to impact. In contrast to the fixed morphology of existing soft artificial muscles, we present a Vacuum-Powered Artificial Muscle (VPAM) with an adjustable operating length that allows customization depending on, or even throughout, a given application. This is achieved through a modular design with cells that can be clipped in a collapsed state and unclipped as desired. To demonstrate the capability of the actuator, we present a case study in 0-6 month infant physical therapy, as a device to assist physical therapy that can grow with the patient. We develop a model of the device and validate its accuracy in a simulated patient setup, demonstrating that the actuator maintains its performance as it grows. Our system can adapt to the growth of an infant during a 6-month treatment regime without the need for actuator replacement, thus creating vast potential for applications ranging from exoskeletons and wearable devices to medical and exploration robots.